The transport burden of rural women in Amuro District, Kogi State (2005)
Women generally play a crucial role in the socio-economic survival and sustenance of their families. Apart from getting involved in rural agricultural production and reproductive activities, women perform household task such as transporting water, and firewood as well as ensuring that their children get to school and health centers whenever they are sick. Most of these functions are carried out on foot especially in the rural areas. The study of' women activity patterns in Amuro District of Kogi State shows that they are mostly responsible for the transportation of water, firewood and agricultural produce in the district. In all probability the time and efforts used on transport activities, would have a devastating impact on the welfare of women. It is therefore imperative to put in place national rural transport policy (NRTP) that is sensitive to the transport burden of rural women in Nigeria.